THE ANALYSIS OF ENTREPRENEURSHIP TREND OF ISLAMIC BOARDING SCHOOL STUDENTS - Kasidi, Kasidi; Satyarini, Marhaeni Dwi; Melati, Inaya Sari (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2021)
The paradigm of graduates applying for jobs in the industrial era 4.0 is no longer relevant to the current employment situation. This paradigm needs to be changed from applying for jobs to becoming entrepreneurial graduates, including graduates from Islamic boarding schools. The objectives of this study were to reveal: (1) the entrepreneurial tendencies of students who were also œsantri (student) in Islamic boarding schools; (2) the factors driving the entrepreneurial desire of œsantri; (3) the influence of entrepreneurial motivation of œsantri on learning achievement in Entrepreneurship course. The research targets were Islamic boarding school students studying in the Study Program of History Education and Citizenship Education, Faculty of Teacher Training and Education, Ivet University, Semarang City, as many as 36 people. Data collection was carried out using questionnaires and interviews. Data processing was performed using descriptive analysis and simple linear regression statistical analysis. The results showed that the entrepreneurial tendency of Islamic boarding school students was quite high. The main driving factor is strong enthusiasm and willingness as well as strong experiences from the environment. However, this study found that high entrepreneurial motivation does not have a significant effect on learning achievement in Entrepreneurship course.